SNP8NRG433E1006 NEUREGULIN-1 GENETIC VARIATION IN BATAKS ETHNIC WITH SCHIZOPHRENIA PARANOID AND HEALTHY CONTROL - Effendy, Elmeida; Loebis, Bahagia; Amir, Nurmiati; Siregar, Yahwardiah (BALI MEDICAL JOURNAL, 2014)
The neuregulin 1 (NRG1) gene which influences the development of white matterconnectivity has been associated with schizophrenia. It influences neuronal migration, synaptogenesis,gliogenesis, neuron-glia communication, myelination, and neurotransmission in the brain and others.NRG1 is located in 8p13, and it is frequently replicated in schizphrenia. SNP8NRG433E1006 geneNRG1 is one of core at risk haplotype of schizphrenia. This study looked forward differencesSNP8NRG433E1006 neuregulin 1 between Bataks ethnic with schizophrenia paranoid and Bataksethnic healthy control. Methods: Batak ethnic with schizophrenia paranoid were recruited andinterviewed with semi-structured MINI ICD-X to establish the diagnosis. All the eligible subjectswere requested their permission for blood sampling. Healthy Batak ethnic were also recruited bymathcing the age and gender. The blood samples went through DNA isolation, Nested PCR, and DNAsequencing. Results: Ninety three subjects were recruited, but only 74 blood samples weresuccesfully sequenced. We found three types of polymorphisms, i.e. G/A allele at base pair (bp) 76,G/T allele at bp 112, and deletion at bp 110 in Batak ethnic with schizophrenia. There were two kindsequences at bp 113-116 in Batak ethnics, and Batak ethnics with ATCG were at higher risk forhaving schizophrenia. This study support that NRG1 is a schizophrenia-susceptibility gene.
Keywords: Schizophrenia paranoid, Single Nucleotide Polymorphism, NRG1 gene